PENGARUH RETURN ON ASSET (ROA), PERTUMBUHAN ASET, DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN (Studi Kasus pada PT. Indofood Sukses Makmur Tbk Tahun 2016 – 2019) - Esih Jayanti; Sovia Tunisa (JURNAL EKONOMI, 2021)
This study aims to test the Return on Asset (X1), Asset Growth (X2), Sales Growth (X3) against the Value Of The Company (Y) in the PT. Indofood Sukses Makmur Tbk. The sample in this study were 48 months financial statements listed on BEI in the period 2016-2019. The result in study were collected through secondary data that was processed and analysed using multiple regression analysis. The method used in this research Purposive Sampling technique. Test the quality of the data used in this study is descriptive statistics. To test the hypotesis in this study using the t-test and f-test. The result of this research data indicate return on asset it shows that has an influence value of the company in PT. Indofood Sukses Makmur Tbk with a significance value 0,000 which means variable ROA has a positive and significant effect to value of the company. For asset growth and sales growth with a significance value 0,024 and 0,000 respectively which means variable asset growth, and sales growth has a positive and significant effect to value of the company. For simulateneous testing, all variables have a significant effect on 0,000. respectively which means variable asset growth, and sales growth has a positive and significant effect to value of the company. Keywords : Return on Asset, Asset Growth, Sales Growth and Value Of The company.